PENGARUH PELATIHAN, PENGAWASAN, DAN DISIPLIN KERJA : Terhadap Kinerja Karyawan PT Bank DKI Cabang Permata Hijau Jakarta Selatan - Faura Zillah (2021)
This study is a quantitative study designed to determine the effect of training, supervision, and work discipline on employee performance. The sample used was permanent employees of PT Bank DKI Permata Hijau Branch, South Jakarta, and researchers used a sample of 73 employees. This research uses probability sampling technique in sampling & sampling method is random sampling. Data collection is done through google form. The analysis technology adopts the inference analysis method, which is carried out through IBM SPSS Statistics 23 in the data processing process & the significance level is 0.05 (5%). The test results are (1) training has a significant effect on employee performance, (2) supervision has a significant effect on employee performance, and (3) work discipline has a significant effect on employee performance (4) training, supervision, and work discipline have a significant effect on employee performance. together. The results of this study, employee performance is determined as much as 89% by training, supervision & work discipline.